Pengaruh Pemberian Buah Mengkudu (Morinda citrifolia) Terhadap Penyakit Dislipidemia - Dian Isti Anggraini; Chania Forcepta; Khairun Nisa (Medula, 2021)
Dyslipidemia is a lipid metabolism disorder characterized by an increase in the lipid fraction in the blood. Dyslipidemia is an important problem because it is a major risk factor for heart disease. The cause of dyslipidemia is caused by disruption of lipid metabolism due to the interaction of genetic and environmental factors. An alternative treatment for dyslipidemia is to use noni (Morinda citrifolia) fruit which contains xeronin, proxeronin, ascorbic acid, linoleic acid, β-carotene, flavonoids and caprylit acid. Compounds that are thought to lower cholesterol are flavonoids. The flavonoid compounds in noni inhibit HMG-CoA reductase so that total cholesterol and LDL will decrease. Noni fruit can also be useful as an antioxidant, anti-inflammatory, antinociceptive, anti-cancer, anti-diabetes and anti-hypertension. Consumption of noni fruit must be careful with gastritis sufferers because noni is acidic. With antidiabetic drugs hypoglycemia and hypotension can occur, because they can reduce blood glucose and potassium levels. The color of urine can be pink to brownish red. May interact with ACE inhibitor drugs, angiotensin II receptor antagonists, potassium-sparing diuretics. May reduce the effect of immunosuppressant drugs.